Problematika Larangan Pengalihan Gadai oleh Mamak dalam Perspektif Hukum Islam - Zikra Rahmi; Aulia Alvitri (Journal of Islamic Law and Wisdom, 2025)
This study aims to determine the status of land ownership that is prevented by the mamak when it is about to be transferred, To find out the reason the  mamak does not allow the mortgage. And to find out the review of Muamalah Fiqh on the reasons for not allowing the mortgage: The research method used is qualitative with data sources originating from KAN, Niniak Mamak, Cadiak Pandai, Bundo Kanduang, Nephews who own land, Mamak Penghulu from those who own land, one of the communities there. For data collection techniques, the researcher used the interview method. The results of the study explain that the land is a high pusako land which is classified as joint property/syirkah property; and the approval of the mother is a form of agreement from all members, and the mother's disagreement is understood as they do not agree to transfer property by one of the clan members, and if one member releases his rights without the approval of other clan members, it is a reprehensible act because it can encroach on the rights of others. This study provides implications that joint rights must be considered if one member wants to release his rights.